Characterization of the flagellar motor composed of functional GFP-fusion derivatives of FliG in the Na(+)-driven polar flagellum of Vibrio alginolyticus - Koike, Masafumi (Biophysics (Nagoya-shi), 2011)
The polar flagellum of Vibrio alginolyticus is driven by sodium ion flux via a stator complex, composed of PomA and PomB, across the cell membrane. The interaction between PomA and the rotor component FliG is believed to generate torque required for flagellar rotation. Previous research reported that a GFP-fused FliG retained function in the Vibrio flagellar motor. In this study, we found that N-terminal or C-terminal fusion of GFP has different effects on both torque generation and the switching frequency of the direction of flagellar motor rotation. We could detect the GFP-fused FliG in the basal-body (rotor) fraction although its association with the basal body was less stable than that of intact FliG. Furthermore, the fusion of GFP to the C-terminus of FliG, which is believed to be directly involved in torque generation, resulted in very slow motility and prohibited the directional change of motor rotation. On the other hand, the fusion of GFP to the N-terminus of FliG conferred almost the same swimming speed as intact FliG. These results are consistent with the premise that the C-terminal domain of FliG is directly involved in torque generation and the GFP fusions are useful to analyze the functions of various domains of FliG.